Growth and lattice dynamics of ultrathin BaO films on Pt(0 0 1). (14th February 2018) - Goian, Veronica; Schumann, Florian O; Widdra, Wolf
Abstract: We report on the surface phonons of long-range ordered BaO thin films grown on Pt(0 0 1). In the thickness range between 4 and 28 ML, we find unstrained BaO(0 0 1)-( 1 × 1 ) bulk-like terminated films which coincide with a Pt(0 0 1)-c( 2 × 2 ) lattice periodicity. The dipole-active lattice vibrations were determined using high-resolution electron energy loss spectroscopy. For all BaO film thicknesses, a single Fuchs–Kliewer phonon-polariton is observed. Its intensity increases and its frequency softens with increasing film thickness. These thickness-dependent properties and the spectral shape are quantitatively discussed on the basis of dielectric theory, where a proper modeling requires three components: the dielectric response of the BaO film itself, the plasmonic response of the metallic substrate, and a weak damping due to a defect-induced doping within the oxide film. For a full description, also the quantization of the phonon wavevector due to the confinement within the film of finite thickness has to be taken into account.